Sustainable Museum Access: A Two-way Street - Levent, Nina; Pursley, Joan Muyskens (Disability Studies Quarterly, 2013)
Many adults who are blind or have low vision are reluctant to visit museums because of disappointing or less-than-welcoming experiences in the past. To attract visually impaired people to your museum, the authors urge you to make outreach and program development a "two-way street," to solicit advice and criticism from a variety of people who are blind or have low vision. In addition, they share issues raised at focus groups they conducted as part of Art Beyond Sight's Multi-Sight Museum Accessibility Study and its Project Access New York program. Key words Accessible museum programs Blind Focus groups museum audience development